EFEKTIVITAS BAKTERI PELARUT POSFAT Bacillus subtilis - Indriani Agustin, ; Yuliani, ; Yuni Sri Rahayu, (Matematika dan Sains, 2009)
The aims of research were to study the enfluence adding of B. subtilis in various concentration to the phosfat concentration and TPH value on the mining land and to find the optimum concentration of B. subtilis. This research was experiment with completely randomized design using one treatment namely the concentration of B. subtilis with four replications. Data obtained were analyzed discriptively. The results of research showed that adding of B. subtilis in various concentration enfluence the increasing of phosfat concentration, decreasing of TPH value and C/N ratio on the mining land. The optimum concentration of B. subtilis was 109 cell/mL.9 cell/mL.